Hydroxysafflor Yellow A and Anhydrosafflor Yellow B Protect Against Cerebral Ischemia/Reperfusion Injury by Attenuating Oxidative Stress and Apoptosis via the Silent Information Regulator 1 Signaling Pathway - Yijia Fangma; Huifen Zhou; Chongyu Shao; Li Yu; Jiehong Yang; Haitong Wan; Yu He (Frontiers in Pharmacology, 2021)
Hydroxysafflor yellow A (HSYA) and anhydrosafflor yellow B (AHSYB) are the main water-soluble compounds in Carthamus tinctorius L. However, studies on the effect of AHSYB on cerebral ischemia/reperfusion (I/R) injury and the therapeutic effect of HSYA by regulating silent information regulator 1 (SIRT1) pathway remain obscure. In this study, we investigated whether the neuroprotective effects of HSYA and AHSYB on oxygen-glucose deprivation/reoxygenation in primary-cultured hippocampal neuronal cells and the middle cerebral artery occlusion and reperfusion model in rats are associated with the regulation of the SIRT1 pathway. In vitro, HSYA and AHSYB increased cell viability, depressed oxidation properties, and reduced neuronal cell apoptosis. In vivo results showed that HSYA and AHSYB effectively reduced infarct volume, improved neurological function, suppressed apoptosis, and decreased the oxidative stress reaction. Besides, RT-PCR and Western blot analysis showed that HSYA and AHSYB increased the mRNA and protein expressions of the main factors in the SIRT1 pathway, including SIRT1, forkhead box O (FOXO) 1, and peroxisome proliferator–activated receptor coactivator 1α (PGC1α), decreased the expression of Bax, and increased the expression of Bcl-2. The results from immunohistochemistry also showed that the expressions of SIRT1, FOXO1, and PGC1α were increased after treatment with HSYA and AHSYB. Furthermore, the neuroprotective effects of HSYA and AHSYB were abolished by EX527 (SIRT1–specific inhibitor). These results indicated that HSYA and AHSYB should be developed into potential drugs for treating cerebral I/R injury via the SIRT1 pathway. Although HSYA and AHSYB have different chemical structures, both of them exert similar neuroprotective properties against I/R injury in vitro and in vivo, which means that AHSYB is also a non-negligible component in safflower.